Optimasi Pembuatan Formulasi Teh Herbal Berbasis Teh Hitam (Camelia sinensis L.), Kulit Jeruk Nipis (Citrus aurantiifolia) dan Serai (Cymbopogon citratus) terhadap Komponen Antioksidan: Optimization of Herbal Tea Based on Black Tea, Lime Peel, and Lemongrass on Antioxidant Components - Adhamatika, Adhima; Rosyadi, A. Sirojul Anam Izza; Sari, Elok Kurnia Novita; Choirun, Annisa'u; Triardianto, Dimas (Jurnal Teknologi dan Mutu Pangan, 2025)
Tea is the most popular beverage product in the world. This high tea consumption trend has encouraged the development of herbal teas by adding other herbal ingredients to enhance the functional components and sensory properties of the resulting tea. Herbal tea is a beverage made from ingredients other than tea leaves, such as flowers, seeds, or roots from various other plants. One such addition is by adding black tea with lime peel and lemongrass. This study aims to determine the optimal formulation of the composition of black tea, lime peel, and lemongrass for antioxidant components. This study used a mixture design experiment design utilizing Design Expert 10 software optimal (custom) design methods. The parameters tested were total phenols, total flavonoids, and antioxidant activity. The results showed that the optimal formulation for producing herbal tea consisted of 75.575% black tea, 16.1% kaffir lime peel, and 8.325% lemongrass, which yielded the most optimal responses: total phenol content of 72.72±0.27 mg GAE/g, total flavonoid content of 40.27±1.44 mg QE/g, and DPPH antioxidant activity of 270.25±1.44 mg TE/g. Therefore, this research is expected to provide an alternative approach for functional herbal tea development.